Proposed new methodology to benchmark N input requirements, N use efficiency and related GHG emissions for cereals - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We propose a new benchmarking method for N inputs and related GHG emissions. In the coming year, we will test this methdology for different arable production systems to validate the approach.